BCN nanosheets templated by g-C3N4 for high performance capacitive deionization. Issue 30 (12th July 2018) - Wang, Shiyong; Wang, Gang; Wu, Tingting; Zhang, Yunqi; Zhan, Fei; Wang, Yuwei; Wang, Jigang; Fu, Yu; Qiu, Jieshan
Abstract : BCN nanosheets show a pore structure with a high specific surface area and are investigated as CDI electrode materials for the first time. Abstract : Capacitive deionization (CDI) is an emerging technology for removing charged ions from saline water and has attracted much attention in recent years. Developing a new electrode material with a reasonable structure is of great significance for obtaining high CDI performance. Herein, two-dimensional (2D) boron carbon nitride (BCN) nanosheets were fabricated using a new approach, which uses g-C3 N4 as both the template and the nitrogen source, boric acid as the boron source and a subsequent pyrolysis process. The as-prepared BCN nanosheets show a pore structure with a high specific surface area and were investigated as CDI electrode materials for the first time. Moreover, the high heteroatom content, with a potential synergistic effect of N and B atoms, results in fast ion diffusion and good charge transfer ability. The BCN nanosheets demonstrate a high salt adsorption capacity of 13.6 mg g −1 at 1.4 V applied voltage when the initial NaCl concentration is 500 mg L −1 . The BCN electrodes also exhibited better cyclic stability over 15 adsorption–desorption cycles. These results indicate that BCN nanosheets should be practicable candidates for high performance CDI electrode materials.